Identifikasi Analisa Mutu pada Proses Refinery PT. XYZ - Aris Toteles; Petrus Jhoy Palilling; Kent Nugroho; Misrianto (Jurnal Riset Teknik Industri, 2026)
Abstract. Quality control in the Refined Bleached Deodorized Palm Oil (RBDPO) refining process is a crucial aspect to ensure product compliance with established specifications, particularly the Free Fatty Acid (FFA) content as a critical quality parameter. Uncontrolled FFA levels can indicate serious process disruptions, especially during the deodorizing stage. This study aims to evaluate the stability of the RBDPO refining process using the Statistical Quality Control (SQC) approach and to identify deviation patterns against the FFA specification limit of < 0.075%. The research method employed is quantitative descriptive-analytical, utilizing testing data from the period of August 1–30, 2025. Analysis results through X̄-R control charts show that FFA values range from 0.042% to 0.097%. Although the majority of the data meets the specifications, the X̄ control chart reveals several points outside the statistical control limits, indicating a shift in the process average due to systemic disruptions in the vacuum system and stripping steam supply. Meanwhile, the R control chart shows that process variability is relatively controlled. These findings confirm that while the variation is stable, the process average is not yet fully under statistical control. Therefore, the continuous application of SQC is essential to maintain the consistency of the final product quality. Abstrak. Pengendalian mutu pada proses pemurnian Refined Bleached Deodorized Palm Oil (RBDPO) merupakan aspek krusial untuk menjamin kesesuaian produk terhadap spesifikasi yang ditetapkan, khususnya kadar Free Fatty Acid (FFA) sebagai parameter mutu kritis. Kadar FFA yang tidak terkendali dapat mengindikasikan adanya gangguan proses serius, terutama pada tahapan deodorizing. Penelitian ini bertujuan untuk mengevaluasi kestabilan proses pemurnian RBDPO menggunakan pendekatan Statistical Quality Control (SQC) serta mengidentifikasi pola penyimpangan terhadap batas spesifikasi FFA < 0,075%. Metode penelitian yang digunakan adalah kuantitatif deskriptif-analitis dengan data pengujian periode 1–30 Agustus 2025. Hasil analisis melalui peta kendali X̄ -R menunjukkan nilai FFA berada pada rentang 0,042–0,097%. Meskipun mayoritas data memenuhi spesifikasi, peta kendali X̄ menunjukkan adanya beberapa titik di luar batas kendali statistik yang mengindikasikan pergeseran rata-rata proses akibat gangguan sistemik pada sistem vakum dan suplai stripping steam. Sementara itu, peta kendali R menunjukkan variabilitas proses relatif terkendali. Temuan ini menegaskan bahwa meskipun variasi stabil, rata-rata proses belum sepenuhnya terkendali. Oleh karena itu, penerapan SQC secara berkelanjutan sangat diperlukan untuk menjaga konsistensi mutu produk akhir.